Differential effects of right and left heart failure on skeletal muscle in rats. Issue 6 (28th September 2020) - Knapp, Fabienne; Niemann, Bernd; Li, Ling; Molenda, Nicole; Kracht, Michael; Schulz, Rainer; Rohrbach, Susanne
Abstract: Background: Exercise intolerance is a cardinal symptom in right (RV) and left ventricular (LV) failure. The underlying skeletal muscle contributes to increased morbidity in patients. Here, we compared skeletal muscle sarcopenia in a novel two‐stage model of RV failure to an established model of LV failure. Methods: Pulmonary artery banding (PAB) or aortic banding (AOB) was performed in weanling rats, inducing a transition from compensated cardiac hypertrophy (after 7 weeks) to heart failure (after 22–26 weeks). Cardiac function was characterized by echocardiography. Skeletal muscle catabolic/anabolic balance and energy metabolism were analysed by histological and biochemical methods, real‐time PCR, and western blot. Results: Two clearly distinguishable stages of left or right heart disease with a comparable severity were reached. However, skeletal muscle impairment was significantly more pronounced in LV failure. While the compensatory stage resulted only in minor changes, soleus and gastrocnemius muscle of AOB rats at the decompensated stage demonstrated reduced weight and fibre diameter, higher proteasome activity and expression of the muscle‐specific ubiquitin E3 ligases muscle‐specific RING finger 1 and atrogin‐1, increased expression of the atrophy marker myostatin, increased autophagy activation, and impaired mitochondrial function and respiratory chain gene expression. Soleus and gastrocnemius muscle of PAB rats did not show significant changes in muscle weight and proteasome or autophagy activation, but mitochondrial function was mildly impaired as well. The diaphragm did not demonstrate differences in any model or disease stage except for myostatin expression, which was altered at the decompensated stage in both models. Plasma interleukin (IL)‐6 and angiotensin II were strongly increased at the decompensated stage (AOB > > PAB). Soleus and gastrocnemius muscle itself demonstrated an increase in IL‐6 expression independent from blood‐derived cytokines only in AOB animals. In vitro experiments in rat skeletal muscle cells suggested a direct impact of IL‐6 and angiotensin II on distinctive atrophic changes. Conclusions: Manifold skeletal muscle alterations are more pronounced in LV failure compared with RV failure despite a similar ventricular impairment. Most of the catabolic changes were observed in soleus or gastrocnemius muscle rather than in the constantly active diaphragm. Mitochondrial dysfunction and up‐regulation of myostatin were identified as the earliest signs of skeletal muscle impairment.